2012
DOI: 10.1242/bio.20121305
|View full text |Cite
|
Sign up to set email alerts
|

Conditional over-expression of PITX1 causes skeletal muscle dystrophy in mice

Abstract: Summary Paired-like homeodomain transcription factor 1 (PITX1) was specifically up-regulated in patients with facioscapulohumeral muscular dystrophy (FSHD) by comparing the genome-wide mRNA expression profiles of 12 neuromuscular disorders. In addition, it is the only known direct transcriptional target of the double homeobox protein 4 (DUX4) of which aberrant expression has been shown to be the cause of FSHD. To test the hypothesis that up-regulation of PITX1 contributes to the skeletal muscle atrophy seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 96 publications
(158 reference statements)
1
52
0
Order By: Relevance
“…4B). Our observation of the angular profiles of the atrophic PD muscle fibers is in line with the previous studies reporting the morphological characteristics for skeletal muscle atrophy (Sakkas et al, 2003;Doppler et al, 2008;Pandey et al, 2012;Hara et al, 2013;Werneck et al, 2013). Additionally, muscle atrophy indicated by significant decline in muscle fiber cross-sectional area (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…4B). Our observation of the angular profiles of the atrophic PD muscle fibers is in line with the previous studies reporting the morphological characteristics for skeletal muscle atrophy (Sakkas et al, 2003;Doppler et al, 2008;Pandey et al, 2012;Hara et al, 2013;Werneck et al, 2013). Additionally, muscle atrophy indicated by significant decline in muscle fiber cross-sectional area (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Pitx2 is required for initiation and progression of myogenic lineage of masticatory muscles, 42 and overexpression of Pitx1 may cause skeletal muscle fiber atrophy. 40 Masseter muscle samples from the side opposite of the chin deviation had increased expression of Pitx1 compared to muscle from symmetric subjects (Table 1). Fast-contracting type II fibers of masseter muscle on this facial side have decreased cell number and cell size, which could be an effect from increased Pitx1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…39 PITX1 , another member of the PITX gene family, produces fiber atrophy when overexpressed in masseter muscle. 40 Collectively, these findings suggest that Nodal Pathway genes are active in adult skeletal muscle and may be key factors in development, growth and maintenance of facial asymmetry. In order to determine if symmetry pathways are active in adult humans we compared gene expression in masseter muscle between dentofacial deformity subjects with and without facial asymmetry.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have found that the PITX1 gene is 10-20 times up-regulated in the muscle fibers of FSHD patients. The role of PITX1 in myopathy was shown in vivo via a tet-repressible muscle-specific PITX1 transgenic mouse model (78,79). The PITX1 transgenic mouse model with overexpression of PITX1 in skeletal muscles demonstrates a similar disease phenotype to the muscular dystrophy seen in FSHD patients.…”
Section: Ao-based Therapy Targeting Pitx1mentioning
confidence: 98%